Pengaruh Pelatihan dan Pengalaman Kerja terhadap Pengembangan Karir Karyawan pada PT Pelabuhan Investama - Noviyani Suprihatini; Usran Masahere (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
PT Pelabuhan Indonesia Investama is the first investment company in Indonesia engaged in the port sector. As a subsidiary of PT Pelabuhan Indonesia (Persero), PT Pelabuhan Indonesia Investama exists as a manifestation of the need for Business Development Support, Capacity Building Funding and Strengthening Risk Management. As an investment company that supports the port sector, PT Pelabuhan Indonesia Investama also supports the acceleration of economic growth in Indonesia. The purpose of this study was to determine the effect of training and work experience on the career development of employees at PT Pelabuhan Indonesia Investama. This study was an employee of PT Pelabuhan Indonesia Investama and the number of samples obtained was 51 respondents. The data collection technique used is non-probability sampling with saturated sampling technique. The approach method in this study uses quantitative methods with observation and questionnaire methods. The data analysis technique used is instrument test, descriptive analysis, classical assumption test, multiple linear regression analysis, coefficient of determination test, and hypothesis testing using SPSS 25. The results of this study indicate that the training variable has a positive and significant effect on career development, experience variable work has a positive and significant effect on career development, training and work experience variables simultaneously have a positive effect on career development